Exemplarity and Judgement: Notes on Kantian Aesthetics - Feyles, Martino (Aesthetica Preprint, 2022)
In the first part of the essay, I will analyse the notion of exemplarity starting from the book of E. Garroni Estetica. Uno sguardo attraverso. I will try to show that, from Garroni’s point of view, the work of art can be considered an exemplary object for two reasons: firstly because it has a normative value, in the sense that it establishes a new rule; secondly because the rule it establishes cannot be translated into conceptual terms. In the second part of the essay, I will use the notion of exemplarity to analyse some passages of the Critique of Judgment. I will argue that the distinction between reflective and determinative judgement can be rethought as a distinction between two different modes of exemplification. Finally, in the last part of the article, I will show that for Kant to present a concept means to exemplify it, and I will distinguish between the different modes of presentation (Darstellung) that are described in the First Critique and in the Third Critique. In particular, I will distinguish between: A) schematic presentation of a pure concept of the intellect; B) presentation of an empirical concept in an example; C) indirect presentation of an idea; D) schematic presentation of an empirical concept not yet known (exemplary case); E) aesthetic presentation of formal purposiveness of nature (in natural beauty); F) presentation (by the genius) of a rule of beautiful art.